Activities and motivations by gender of widowed elderly living with extended family from two rural communities in Rizal - Arcilla, Audrey Lynn A.; Garcia, Fatima Ann S.; Roldan, Aurorita T. (Quezon City: College of Home Economics, University of the Philippines Diliman, c2017.)
This paper described the activities and motivations by gender of low income, widowed elderlies living with their extended family. The participants were 15 female and 15 male elderlies aged 60-75 years old that are physically independent and lived in two rural communities within the Province of Rizal. They were selected through purposive sampling using the snowball method. A semi-structured interview was used to gather data. The low income, widowed elderlies were interviewed on the activities that they engage in, as well as its frequency, location and who they do their activities with. The elderly were also asked on their reasons for doing their activities. From the stated reasons the researchers determined if they are internally or externally motivated in the activities which they engage in. Themes arose from the analysis of the study. The findings showed that the respondents engaged in productive and recreational activities. Four of these are in line with their corresponding developmental tasks as revealed in the literature while two developmental tasks were not significantly stated in their activities. There are activities which males do more such as carpentry and farming as livelihood as well as watching TV. The activities which females do more are household tasks, selling as livelihood, community involvement, and going to mass. The activities which both genders do are food related activities and taking care of dependents. From the reasons stated, it was seen that the activities of the elderly were internally and externally motivated. The study is seen to be able to contribute to the growing body of knowledge on the state of the elderly in the Philippines, which could lead to further studies to raise awareness and to improve the welfare of the elderly in the country.
submitted June 2017
Thesis (B.S. Family Life and Child Development)--University of the Philippines Diliman.
Keywords: Older people -- Philippines -- Rizal; Older people -- Life skills guide